Thermodynamically-equilibrium LCST phase diagram of PCL/SAN mixtures determined by thermal analysis: Opposing effects of hydrophilic and hydrophobic silica nanoparticles - Maghoul, Ali; Salkhi Khasraghi, Samaneh; Khonakdar, Hanieh; Mousavi, Seyed Rasoul; Hemmati, Farkhondeh; Kühnert, Ines; Leuteritz, Andreas; Nobre, Marcos A.L. [UNESP]; Khonakdar, Hossein Ali (Elsevier, 2023)
In this work, the isothermal crystallization kinetics of PCL in PCL/SAN blend and PCL/SAN/nanosilica nanocomposite systems has been applied as a useful and sensitive variable for determining the LCST phase diagram. By eliminating the impacts of kinetic variables, the variations in the equilibrium LCST phase boundary of PCL/SAN mixtures were evaluated. The presence of hydrophobic nanoparticles shifted the equilibrium LCST phase diagram to higher temperatures as expected owing to the compatibilization effect of nanoparticles, while the hydrophilic nanoparticles shifted it to lower temperature. The preferential migration of hydrophilic nanosilica into SAN-rich phase with slower molecular dynamics caused larger viscoelastic asymmetry of polymeric phases and consequently, lower area of phase miscibility window. In contrast, the addition of hydrophobic nanosilica with better dispersion state and no preferential localization in PCL/SAN blend resulted in a shift of LCST phase diagram to higher temperatures.
Keywords: Crystallization; Nanocomposites; Phase behavior; Poly(styrene-co-acrylonitrile); Poly(ε-caprolactone)